2021
DOI: 10.1038/s41598-021-84134-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profiles in older males and females

Abstract: Males and females are subject to differences in cognitive processing strategies, i.e. the way males and females solve cognitive tasks. So far primarily reported for younger adults, this seems to be especially important in older adults, who also show sex differences in cognitive impairments. Therefore, the aim of the current study was to examine the older adult population with respect to cognitive profiles derived from a large variety of cognitive functions. Using an exploratory component analysis with consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Sex differences have been described in previous research ( Tamayo et al, 2012 ; Kestens et al, 2021 ), with authors encouraging to use sex-stratified analysis when cognitive decline is evaluated ( Jockwitz et al, 2021 ); however, others have not found significant difference between males and females in cognitive tasks ( Kessels et al, 2008 ) which is in accordance with the Gender Similarities Hypothesis (e.g., males and females are quite similar on most psychological variables; Hyde, 2005 ).…”
Section: Discussionsupporting
confidence: 60%
“…Sex differences have been described in previous research ( Tamayo et al, 2012 ; Kestens et al, 2021 ), with authors encouraging to use sex-stratified analysis when cognitive decline is evaluated ( Jockwitz et al, 2021 ); however, others have not found significant difference between males and females in cognitive tasks ( Kessels et al, 2008 ) which is in accordance with the Gender Similarities Hypothesis (e.g., males and females are quite similar on most psychological variables; Hyde, 2005 ).…”
Section: Discussionsupporting
confidence: 60%
“…For instance, studies on the effects of sex/age in perceptual thinking, decision-making, or behavioral changes generate stereotypes that can stigmatize women/men at different levels. While some of these studies did not find differences in everyday performed activities ( Hirnstein et al, 2019 ), others found that women/men adopt different strategies to process cognitive tasks ( Jockwitz et al, 2021 ). Indeed, during the aging process, women and men display notorious differences regarding susceptibility to some pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological changes with age have been more attractive since the life expectance of the population increased ( López-Otín et al, 2013 ; Jockwitz et al, 2021 ). Due to the growth of the older human population, recent investigations allocate their observations to determine the cognitive status of older people, correlating how they use the information to resolve a task ( Jockwitz et al, 2021 ). However, numerous considerations should be included, i.e., previous experience and brain status during acquisition or retrieval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FiPaT is not affected by the sex variable, probably because the cognitive component weighs more than the motor one. Accordingly, previous literature does not report sex differences for executive and attentional functions [ 15 , 16 ]. Furthermore, the number of errors correlates with age and not with education and this is in line with the natural course of brain skills [ 17 ].…”
Section: Discussionmentioning
confidence: 94%